ALAM, MANUSIA, DAN SPIRITUALITAS - Yasmin Kartikasari (Fakultas Seni Rupa dan Desain ITB, 2011)
How is the position of man in existence in the world? There needs to be a differentiator to declare the existence of a person, including the presence of nature as the existence of human, and vice versa. However, whether the distinction should be separate from our identity? What if the difference is precisely the part of ourselves that need to be aware of its existence. Humans are trapped in the separation with other niches. Humans forget to see everything as a unity, complement each other. Each component, element, entity, has the function and nature of each; whose existence is to feed the other, not deadly. Keywords: relation, unity, spiritual